Public Lecture: That This Profession May Not Die: The Need To Flush Out Miscreants From The Nigerian Legal Profession - Muhammad, Ibrahim Tanko (Journal of Sustainable Development Law and Policy, 2025)
One of the key hindrances to sustainable development and economic growth in Nigeria is the problem of corruption. For many years, discussions on corruption inevitably focused on political abuse of powers and privileges and wanton disregard of the rule of law. Events of the last decade however sadly reveal that corruption, nepotism, and indiscipline have equally taken prominent places in the Nigerian legal profession, ranging from the bar, bench and the legal academia. Most alarming is the geometric rise in instances of corruption in our higher institutions of learning; ranging from prevalent sharp practices in admissions, examinations, research, teaching, tenure and academic promotions. This paper examines the challenges of endemic and systemic corruption in the Nigerian legal profession. The paper adopts a crosscutting approach to discuss how perennial instances of corruption threaten the nobility and growth of the Nigerian legal profession. It proposes a holistic purging of the bench, practicing bar, and the legal academia to name, shame and expel miscreants, in order to restore the age long discipline and dignity of the Nigerian legal profession.